A cost-effective method to measure delayed deformations of building materials - Fathi, Ahmad (2022)
Characterization of deformation related properties like creep, moisture expansion, drying shrinkage, and others, usually require a high number of specimens and long-term tests. Traditional measuring methods, such as LVDTs or Strain Gauges, end up being expensive, considering the initial cost, the time they are allocated to the experimental campaign, and the required data acquisition systems. This research proposes an innovative cost-effective solution to measure strains on building material using microscope scale images. The main features of the method are: a) cost-effective, b) appropriate for long-term tests, c) possibility of using with high number of specimens, d) good precision (<3μm), and e) open source. The development is being described into two stages including methodological aspects and validation which are discussed in this work. The developed method is based on a sliding ruler that is connected to the specimen. The ruler has two parts (one fixed and one movable), and their relative movement, as consequence of the deformation, is monitored with indicators. Using a USB microscope to capture sequential images, it is possible to determine the evolution of the deformation using artificial vision algorithms. This methodology was validated with traditional measurement methods.